Depressive symptoms among people living with HIV in permanent supportive housing: Findings from a community‐based participatory study in Vancouver, Canada. Issue 8 (17th May 2022) - Vorobyova, Anna; Braley, McKenzie S.; Burgess, Heather; Grieve, Sean; Lyndon, Sharyle; Wesseling, Tim; Parashar, Surita
Abstract: Permanent supportive housing (PSH) is an intervention addressing housing needs among marginally housed individuals. Little is known about whether and how PSH influences depressive symptoms among people living with HIV (PLHIV). This article shares results from a community‐based study that, in 2016–2017, interviewed 24 residents of a PSH facility designated for PLHIV in Vancouver, Canada. The themes of taking control; social connectedness; conviviality; and relationships and supports described how the PSH environment affected depressive symptoms among the residents.